Cultures of conversions - Bremmer, Jan N.; Bekkum, Wout Jac. van; Molendijk, Arie L. (Groningen studies in cultural change ;, 2006)
In the terms of Durkheimian sociology, conversion is a fait social. Although they are rarely treated as a cultural phenomenon, conversions can obviously be examined for the norms, values and presuppositions of the cultures in which they take place. Thus conversion can help us to shed light on a particular culture. At the same time, the term evokes a dramatic appeal that suggests a kind of suddenness, although in most cases conversion implies a more gradual process of establishing and defining a new - religious - identity. From 21-24 May, 2003, the University of Groningen hosted an international conference on 'Cultures of Conversion'.